Muslim Consumer Behavior in the Halal Lifestyle Era: A Conceptual Analysis Based on Maslahah Mursalah - Alwi, Muhammad; Adam, Muhammad; Yusuf, Hardiyanti (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
The development of halal lifestyle has fundamentally changed Muslim consumption patterns, from merely fulfilling biological needs to manifesting religious identity, social ethics, and modern aspirations. This article examines the dynamics of Muslim consumer behavior in the context of halal lifestyle trends by highlighting the religious, social, psychological , and economic factors that influence decision-making. Through a conceptual study based on a systematic literature review and recent empirical data, it is found that Muslim consumers are now increasingly active, critical, and oriented towards ethical awareness. Consumption decisions are formed through the interaction between normative sharia values, community social norms, perceived risk benefits, and limited purchasing power. This study highlights the limitations of conventional consumer behavior models that tend to ignore normative aspects, so that a new approach based on maslahah mursalah is needed as an ethical and rational foundation. This article offers a conceptual model of consumer behavior based on perceptions of maslahah that explains the relationship between religious intentions, actual decisions, and the socio-economic impacts of consumption. Its practical implications provide direction for the halal industry, regulators, and academics in designing marketing strategies, certification, and consumer education that support the achievement of maqāṣid al-sharī'ah and the sustainability of the global halal market.